PLEURAL EFFUSION IN A COVID-19 PATIENT - Aritonović Pribaković, Jelena M; Milica,; Milošević, Jelena; Janićević, Aleksandra (Srpski medicinski časopis Lekarske komore, 2021)
Introduction/Aim: Pleural effusions are rarely seen on computerized tomography (CT) or radiography (X-ray) images of the chest, in coronavirus disease of 2019 (COVID-19). When present, they usually occur late in the course of the disease; they are mostly unilateral but can also be bilateral, and are absorbed after two days. Studies have also shown that pleural effusions occur primarily in the elderly and individuals with underlying respiratory disease. The incidence of respiratory failure and acute respiratory distress syndrome, as well as the mortality rates are higher in patients with pleural effusion than in patients withoutit. Our aim is to report a case that is different from the most commonly described cases in available literature.Patient presentation: We present a 49-year-old, comorbidity-free COVID-19 patient, who developed pleural effusion on the 10th day of hospitalization. The pleural effusion was unilateral and did not appear on a repeat lung radiography after four days. Except an elevated platelet count, the blood count parameterswere in the reference ranges, while the value of CRP was slightly elevated. The patient was discharged with a good general health status, after 16 days of hospitalization.Conclusion: This case provides insight into the course and prognosis of the COVID- 19 disease that is different from what has been reported in previously published papers and shows that pleural effusions do not occur only in elderly patients with comorbidities and a severe clinical presentation of the COVID-19 infection.
Keywords: COVID-19; pleural effusions; chest radiography